2023
DOI: 10.1093/mnras/stad3145
|View full text |Cite
|
Sign up to set email alerts
|

QUIJOTE Scientific Results – XVII. Studying the anomalous microwave emission in the Andromeda Galaxy with QUIJOTE-MFI

M Fernández-Torreiro,
R T Génova-Santos,
J A Rubiño-Martín
et al.

Abstract: The Andromeda Galaxy (M31) is the Local Group galaxy that is most similar to the Milky Way (MW). The similarities between the two galaxies make M31 useful for studying integrated properties common to spiral galaxies. We use the data from the recent QUIJOTE-MFI Wide Survey, together with new raster observations focused on M31, to study its integrated emission. The addition of raster data improves the sensitivity of QUIJOTE-MFI maps by almost a factor 3. Our main interest is to confirm if anomalous microwave emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…A recent study by Harper et al (2023) reported the marginal detection of AME in M31, suggesting that it may not be uniformly distributed throughout the entire galaxy. Conversely, the study by Fernández-Torreiro et al (2024) presented a contrasting view, strongly advocating for the presence of AME in M31. In addition, Tibbs et al (2018) reported an AME-like source in a small spiral galaxy in the Local Group, M33, in its global spectral energy distribution (SED).…”
Section: Introductionmentioning
confidence: 97%
“…A recent study by Harper et al (2023) reported the marginal detection of AME in M31, suggesting that it may not be uniformly distributed throughout the entire galaxy. Conversely, the study by Fernández-Torreiro et al (2024) presented a contrasting view, strongly advocating for the presence of AME in M31. In addition, Tibbs et al (2018) reported an AME-like source in a small spiral galaxy in the Local Group, M33, in its global spectral energy distribution (SED).…”
Section: Introductionmentioning
confidence: 97%